Kinematic and neuro-muscular adaptations following a training program for the underwater dolphin kick - Elipot, M.; Hellard, P.; Puel, F.; Morlier, J.; Cazalets, J.-R. (XIII th International Symposium on Biomechanics and Medicine in Swimming Proceedings, 2018)
The main aim of this work was to apply to a group of young swimmers an 8 weeks training program focused on the underwater dolphin kick skills and identify the main kinematic and neuro-muscular adaptations resulting of it. The kinematic parameters were measured using a set of cameras placed under the water and in 3D: These parameters were the instantaneous velocity, the amplitude (trajectory corrected vertical distance covered by the end-effector during a single kick), the frequency, the distance per kick (horizontal distance covered by the centre of mass during a single kick), the flexion/extension angles for the main joints (decrease/increase of the joint angle on the sagittal plan), the angles of attack for the main limbs, and the motor coordination between the mainjoints. The muscles activities were measured using EMG units placed on the quadriceps, the hamstrings, the calf, the gluteal, the lumbar. The time of contraction, the quantity of contraction and the coordination between each muscle activations were then calculated. The main results of this study show an increase of the underwater kicking velocity for 7 of the 8 swimmers that took part to the program. It appeared that the ratio frequency/amplitude was adjusted with an increase of the frequency (reaching 2.5 kicks/second) and a decrease of the amplitude. The study also pointed out the upper body limbs angles of attack were all reduced for all of the swimmers. The results have also shown that each swimmer modified their joint angles using different strategies. Some joints` angles were sometimes increased or decreased depending on the swimmers and no global trend could be identified. However the coordination analysis tends to show that swimmers started developing a synergistic coordination between their joints. EMG data showed that the type of contraction of the muscles had changed. For the lower limbs muscles, the duration of contraction got shorter and the quantity of contraction more important. For the lumbar muscles, the time of contraction got longer and the quantity of contraction lower. The results consequently showed that for the gluteal, hamstring, quadriceps and calf muscles the profile of activation got closer to a phasic contraction, while for the lumbar muscle the profile of activation got closer to a tonic contraction. The sequence of contraction of the muscles was also modified.